Diagnostic evaluation of an in-house developed single-tube, duplex, nested IS6110 real-time PCR assay for rapid pulmonary tuberculosis diagnosis. (September 2018) - Leung, Kenneth Siu-Sing; Siu, Gilman Kit-Hang; Tam, Kingsley King-Gee; Ho, Pak-Leung; Wong, Samson Sai-Yin; Leung, Eunice Ka-Chun; Yu, Shi Hui; Ma, Oliver Chiu-Kit; Yam, Wing-Cheong
Abstract: Objective: To perform a prospective evaluation on the diagnostic performance of an in-house developed, duplex nested IS6110 real-time Polymerase-Chain-Reaction (PCR) assay (IS6110-qPCR assay) for rapid pulmonary TB diagnosis. Methods: A total of 503 sputum specimens were prospectively collected from July 2016 to November 2016. Diagnostic accuracy and optimal cut-off Cycle-threshold (Ct) value for IS6110-qPCR assay was determined by Receiver Operating Characteristic (ROC) curve. Using the optimal cut-off Ct, diagnostic performance of IS6110-qPCR assay was assessed with reference to both bacteriological and clinical information. Meanwhile, limit of detection (LOD) was calculated using Mycobacterium tuberculosis H37Rv as reference strain. Result: ROC curve analysis of IS6110-qPCR assay showed a high Area Under the Curve (AUC) value (0.948) with optimal Ct value at 24.140. Prospective analysis of IS6110-qPCR assay with cut-off Ct = 24.140 showed a high overall sensitivity and specificity of 97.2% and 99.7%, respectively. No cross reactivity was observed among all non-tuberculous mycobacteria specimens in this study. LOD analysis on MTB-spiked sputum showed an average detection limit of 5.0 CFU/mL at Ct = 23.18 (±SD, 0.57). Conclusion: IS6110-qPCR assay is a highly accurate and cost-effective assay developed for primary screening of suspected TB cases, which is particularly suitable for regions with limited resources but high TB burden.